Peroral endoscopic myotomy (POEM) is effective in treatment of noncardiac chest pain caused by hypercontractile esophageal motility disorders: results of the POEM-HYPE-Study - Albers, David; Frieling, Thomas; Dakkak, Dani; Kuhlbusch-Zicklam, Rita; Töx, Ulrich; Gittinger, Mathis; Schumacher, Brigitte (Zeitschrift für Gastroenterologie, 2018)
Background Noncardiac chest pain (NCCP) is recurrent angina pectoris-like pain without evidence of coronary heart disease in conventional diagnostic evaluation. In gastroenterology, managing of patients with NCCP is ambiguous to detect gastroesophageal reflux and hypercontractile esophageal motility disorders. Recently, peroral endoscopic myotomy (POEM) was established as treatment option in achalasia. However, limited data exist on the effectivity of POEM in NCCP with hypercontractile esophageal motility disorders.Material and methods In this prospective study (POEM-HYPE), we evaluated 14 patients with NCCP and hypercontractile esophageal motility disorders (type III achalasia, n = 7; hypercontractile esophagus, n = 6; distal esophageal spasm, n = 1). All patients underwent standardized diagnostic work-up including esophagogastroduodenoscopy with esophageal biopsies, high-resolution esophageal manometry, and combined intraluminal impedance and pH testing before and 3 weeks after POEM. A standardized symptom questionnaire was disposed before POEM, 3 weeks after, and every 6 months after the POEM.Results After POEM, 12 patients showed significant symptom relief (pre-Eckardt score: 7.78 ± 1.47, 3 weeks post: 1.64 ± 1.44, 6 months: 2.0 ± 1.84 and 1.86 ± 1.89 after 15.0 ± 10.0 months post-intervention). High-resolution manometry showed significant reduction in integrated relaxation pressure (pre-POEM: 24.74 ± 18.9 mm Hg, post-POEM: 13.8 ± 16.5 mm Hg) and distal contractile integral (pre-POEM: 2880 ± 3700 mmHg*s*cm, post-POEM: 1109 ± 1042 mmHg*s*cm). One lesion of the submucosal tunnel occurred as a moderate adverse event and was handled endoscopically. The long-term clinical success rate was 85.7 %. No severe gastroesophageal reflux occurred after interventions. Two patients required secondary therapy with injection of botulinum toxin in the tubular esophagus and balloon dilation.Conclusion The results suggest that POEM is an effective and safe therapeutic option for patients with NCCP and hypercontractile esophageal motility disorders.
Keywords: noncardiac chest pain (NCCP); hypercontractile esophageal motility disorder; peroral endoscopic myotomy (POEM); endoscopic therapy; achalasia type III; Jackhammer esophagus; distal esophageal spasm